(untitled) (Cadernos de Sociomuseologia, 2016)
This thesis aims to study the architectural heritage, recognized by the State and under governmental trust and that houses a museum entity, as a museum patrimony, according to the Sociomuseology principles. ln some cases, architecture may be considered a patrimony that holds another patrimony. Seen even when it’s decided not to enter a museum, the architecture treated as a museum object can be used to communicate an era, its symbols, the social relationships that made its edification possible and its constructive technique, making History emerge again and, with it, elements that can activate to the community the bonds of belonging to their constructed patrimony. Aiming to study the practical application of the hypothesis and later identifying the points that can be used in the musealization of the architectural patrimony of other museums in buildings under governmental trust, it has been developed, throughout the research, a Project of Musealization of the Architectural Patrimony for the Museu Vivo da Memória Candanga. The thesis is concluded by highlighting the characteristics of architecture as a potential object of a museum, capable of acting in museum processes, aiming social inclusion, identity recognition and practices related to citizenship and education about patrimony. Keywords: Architecture, Museology, Sociomuseology, Museu Vivo da Memória Candanga, Architectural heritage